Sustainability communication interdisciplinary perspectives and theoretical foundation - Godemann, Jasmin 1973-; Michelsen, Gerd 1948- (Springer, 2011)
Modern and professional communication is required to realise the goal of sustainability in society. This book develops a theoretical and empirical framework, integrating interdisciplinary perspectives from communications theory, psychology, sociology, educational sciences, systems theory and constructivism. Its aim is to inform the establishment of sustainability communication. Complementing this theoretical framework, the book provides methods and concepts in a range of fields such as corporate practice, education and media. The book addresses the scientific community and students as well as communicators in all categories of sustainability communication.